Nickel and platinum in high-temperature H2O + HCl fluids: Implications for hydrothermal mobilization. (1st March 2018) - Scholten, Lea; Watenphul, Anke; Beermann, Oliver; Testemale, Denis; Ames, Doreen; Schmidt, Christian
Abstract: The dissolution of NiS and NiAs (nickeline) in 0.1 and 1 molal HCl at 400 °C, 80 MPa, and of PtAs2 (sperrylite) and Pt metal in 1 and 6.86 molal HCl at 500 °C, 80 MPa was studied in-situ using synchrotron radiation X-ray fluorescence and absorption spectroscopy. The Pt concentration in the fluid averaged 8 · 10 −5 molal (12.8 ppm) during dissolution of Pt metal in 6.86 molal HCl, and was below the minimum detection limit ( mdl ; 2.6 · 10 −5  molal) in all other experiments. Dissolution of NiS was congruent or nearly congruent. Equilibrium was attained rapidly in about 250 min at an initial HCl concentration of 1 molal HCl, and in about 500 min at 0.1 molal HCl. Addition of HCl resulted in a large increase in the Ni solubility from 7.2 · 10 −3 molal Ni (423 ppm) at 0.1 molal HCl to 8.72 · 10 −2 molal Ni (4959 ppm) at 1 molal HCl. Dissolution of NiAs in 0.1 and 1 molal HCl was incongruent. A steady state was not reached even at a run duration of more than 16 h, and the maximum recorded Ni concentrations in the fluid were much lower than the Ni solubility in the corresponding experiments with NiS at the same HCl molality. Measured K-edge XANES spectra in comparison with literature data indicated that arsenic in the fluid was present as As(V) and that nickel complexed with Cl and H2 O as tetrahedral [NiCl2 (H2 O)2 ] 0 and [NiCl3 (H2 O)] − and octahedral [NiCl2 (H2 O)4 ] 0 species. In addition, Raman spectra of H2 O + NiCl2 and H2 O + NiCl2  + HCl solutions and of H2 O + HCl fluids reacted with NiS crystals were acquired at temperatures ( T ) up to 600 °C and pressures ( P ) up to 1.15 GPa. All spectra at T   ≥  300 °C and P  < 600 MPa showed a previously not reported Raman peak at ∼280 cm −1 together with a weaker peak at ∼230 cm −1 . These peaks can be assigned to Ni–Cl vibrations. The band at 280 cm −1 was not detected at the other P-T conditions. Based on calculated vibrational frequencies available in the literature, it may stem from the species [NiCl4 ] 2– or [NiCl2 (H2 O)4 ] 0, although particularly the first assignment is in conflict with the information from published XAS data. The results of this study demonstrate that nickel is readily mobilized by acidic chloridic hydrothermal fluids, but platinum remains practically immobile in such fluids at any HCl concentration that is conceivable to occur in nature. Therefore, the enrichment of Pt relative to Ni in footwall-type deposits in the Sudbury District and the growth of large sperrylite crystals are likely related to magmatic processes. Furthermore, the experiments point to the importance of redox reactions for the mobilization and precipitation of arsenides and suggest that arsenate species are more stable in hydrothermal fluids than previously thought.